2017
DOI: 10.1159/000475502
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of <b><i>Galectin-3</i></b> Gene Polymorphisms with Risk and Prognosis of Cervical Cancer in Chinese Populations: A Case-Control Study

Abstract: Background: This study explores correlations of galectin-3 gene polymorphisms (rs4644, rs4652, and rs11125) with cervical cancer risk and prognosis in Chinese populations. Methods: A total of 126 patients with cervical cancer were selected to form the case group, and 102 healthy people were selected for the control group following a physical examination. 3 polymorphisms were detected by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: The distribution frequencies of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The presence of a SNP (rs4644) in the galectin-3 gene, a substitution of Proline 64 with Histidine, results in cells with increased chemotaxis, chemo-invasion, angiogenesis, apoptosis resistance in vitro, tumor formation in vivo and an increased susceptibility to breast cancer (Nangia-Makker et al 2007;Balan et al 2008). Subsequent studies reported an association of this SNP to prostate cancer and cervical cancer susceptibility (Meyer, 2013, Fang, 2017, rheumatoid arthritis (Hu, 2011) and drug resistance (Mazurek, 2011) via β-catenin pathway. It would be interesting to establish whether galectin-3 germline mutation is associated with cancer stemness.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a SNP (rs4644) in the galectin-3 gene, a substitution of Proline 64 with Histidine, results in cells with increased chemotaxis, chemo-invasion, angiogenesis, apoptosis resistance in vitro, tumor formation in vivo and an increased susceptibility to breast cancer (Nangia-Makker et al 2007;Balan et al 2008). Subsequent studies reported an association of this SNP to prostate cancer and cervical cancer susceptibility (Meyer, 2013, Fang, 2017, rheumatoid arthritis (Hu, 2011) and drug resistance (Mazurek, 2011) via β-catenin pathway. It would be interesting to establish whether galectin-3 germline mutation is associated with cancer stemness.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 positive expression in cervical cancer patients with very low or negative levels of p16 (onco-protein, used as a HPV marker), was also found to be correlated with poor prognosis in OS analyses 52. Additionally, the comprehensive case control investigation of galectin-3 gene polymorphisms (rs4644, rs4652 and rs11125) demonstrated a positive prognostic correlation in Chinese cervical cancer patients 53. Polymerase chain reaction-restriction fragment length polymorphism detected significantly increased distribution of the CC+CA genotype of rs4652 and AT+TT genotype of rs11125 in the cervical cancer group compared with healthy control.…”
Section: The Role Of Galectin-3 In Gynecological Cancersmentioning
confidence: 89%
“…[22] However, we did not analyze the response to chemotherapy of our patients, since all patients underwent resection surgery. Regarding the possible roles of rs4644 and rs4652 variants in the incidence of several cancer types, [13][14][15][16][17] the sample size of the present study could be enlarged to reach statistical significance for the genotype and allele distribution between the patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Besides, rs4652 variant was thought to contribute to the susceptibility and chemotherapeutic drug resistance in gastric carcinoma. [ 16 ] Recently, Fang et al[ 17 ] recorded that allele C of rs4652 variant might be risk factor for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%